Globalization and Islam - Abdul Razak, Mohd Abbas (Greenhaven Publishing, 2020)
During the Golden Age of Islam (750-1258), Muslims were in the forefront in conquering knowledge through scientific research, exploration and expeditions. In their pursuit of mastering new knowledge and technology, Muslims were prepared and open to the idea of learning all that is positive from the earlier civilizations. As such they borrowed ideas from the Indians, Persians and Greeks as a way of enriching their own civilization. While pioneering into many scientific research works, Muslims were also equally interested in mastering Greek philosophical thoughts and the human sciences. The zeal they had for philosophy brought them closer to the ideas of the ancient philosophers like Socrates (469BC-399BC), Plato (427BC-347BC), Aristotle (384BC-322BC) and others. In realizing the fact that not all ideas of the Greek philosophers were acceptable to their Islamic worldview, early Muslim scholars used the approach of adopt, adapt and assimilate or integrate. Through this methodology, the early Muslim scholars took all those ideas which were non-contradictory to their religious values and faith. The scholars of the Golden Age of Islam not only borrowed ideas from others but they went on to further expand and come up with some new, original and innovative ideas. This was the spirit and culture of learning that was prevalent during the early Muslim era of knowledge expansion and exploration. Similarly, Western scholars too had borrowed ideas from Muslim scholars during the Golden Age of the Muslims. Europeans learnt philosophical ideas of the Greek from the translated and annotated works done by the Muslim scholars. Moreover, they also learnt from many pioneering works done by Muslim scholars and scientists in the field of medicine, astronomy, chemistry, mathematics, algebra, trigonometry, etc. At the moment, only a few Western scholars duly acknowledge the great contribution made by the Muslims in inspiring and introducing the West towards science and scientific explorations.